2008
DOI: 10.1111/j.1551-2916.2008.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Synthesis and Characterization of Potassium Polytitanate Ceramic Precursors with Varied TiO2/K2O Molar Ratios

Abstract: Semi‐crystalline potassium titanates, useful as precursors to produce composite materials and coatings, were synthesized by thermal treatment of powdered TiO2 in molten mixtures of KNO3 and KOH at 450°–550°C. The products obtained had similar structures of laminar crystals, aggregated in particles of about 3 μm of n=TiO2/K2O molar ratio in the range 2.8–6.0. The value of n could be regulated by the temperature of synthesis, the weight ratio of [KOH]/[KNO3] in the molten salt mixture, and the number of water wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 21 publications
1
25
0
4
Order By: Relevance
“…The obtained glass had the following chemical composition (wt%): SiO 2 (9. The potassium polytitanate used as a precursor material to form crystalline fiber-shaped titanate was synthesized according to the stated in the literature [15], that is by heat treatment of the mixture, consisting of TiO 2 powder (anatase, Aldrich, 99%), KOH (Aldrich, 99%) and KNO 3 (Aldrich 98%) with a weight percent relation of 1:1:8, respectively. The heat treatment was performed at 500 8C for 2 h followed by washing with distilled water and drying at 60 8C for 4 h. The powdered product of the synthesis showed a molar ratio of TiO 2 /K 2 O $ 5.3 according to energy dispersive spectroscopy (EDS) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained glass had the following chemical composition (wt%): SiO 2 (9. The potassium polytitanate used as a precursor material to form crystalline fiber-shaped titanate was synthesized according to the stated in the literature [15], that is by heat treatment of the mixture, consisting of TiO 2 powder (anatase, Aldrich, 99%), KOH (Aldrich, 99%) and KNO 3 (Aldrich 98%) with a weight percent relation of 1:1:8, respectively. The heat treatment was performed at 500 8C for 2 h followed by washing with distilled water and drying at 60 8C for 4 h. The powdered product of the synthesis showed a molar ratio of TiO 2 /K 2 O $ 5.3 according to energy dispersive spectroscopy (EDS) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The potassium polytitanate, obtained by molten salt method [15], was selected as another component of the system. This new precursor material of K 2 OÁnTiO 2 chemical composition has semi-crystalline or amorphous structure; however, an additional heat treatment at temperatures higher of 800-850 8C promotes its crystallization obtaining fiber-shaped potassium tetratitanate or hexatitanate depending on the value of n = TiO 2 / K 2 O in the original composition.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium polytitanat (PPT) was produced by crystallization technology from a mixture of melted potassium hydroxide (KOH, chemically pure, Russia) and nitrate (KNO 3 , chemically pure, Russia) and titanium dioxide (TiO 2 , chemically pure, Russia) [6,7] on the industrial production line on the basis of LLC "Nanocomposite" Saratov, Russia. Low density polyethylene (HDPE) grade 273 (LLC "Stavrolen", Russia) was used as polymer matrix for preparation of composites.…”
Section: Experimental Partmentioning
confidence: 99%
“…Several years ago, the authors showed that the most perspective and effective approach to structure polymeric materials was the transition to the regulation of materials properties on submicron and nanoscale level [4,5]; where relatively new class of ceramic oxide fillers -potassium polytitanates -seemed to be of high interest in terms of research and practical use. The most effective and the least expensive method for polytitanates production is crystallization from melted salts [6,7]. Depending on synthesis conditions and chemical composition, they are either amorphous compounds with layered structure (potassium polytitanates) or crystalline submicro-and nanofibers (potassium tetra-, hexa-, or octatitanates) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium polytitanate (KPT) synthesized following the procedure of [8] during working of titanium oxide powder (rutile, average particle size 7 mm) in melt containing KOH and KNO 3 in the ratio 1 : 8 at temperature 500°C was used for the experiments. The product obtained was washed with distilled water and dried in a desiccator at 60°C.…”
mentioning
confidence: 99%